thats the answer i keep getting but it is apparently:
2/15(3x-2) (x+1)^3/2
your both right
... factorize...
2/3x(x+1)^(3/2) - 4/15(x+1)^5/2) + k =(x+1)^(3/2)(2x/3- 4(x+1)/15) + k =(x+1)^(3/2)((10x- 4(x+1))/15)) + k =(x+1)^(3/2)((10x- 4x-4))/15)) + k =(x+1)^(3/2)((6x-4))/15)) + k =(2/15)(3x-2)(x+1)^(3/2) + k
2/3x(x+1)^(3/2) - 4/15(x+1)^5/2) + k =(x+1)^(3/2)(2x/3- 4(x+1)/15) + k =(x+1)^(3/2)((10x- 4(x+1))/15)) + k =(x+1)^(3/2)((10x- 4x-4))/15)) + k =(x+1)^(3/2)((6x-4))/15)) + k =(2/15)(3x-2)(x+1)^(3/2) + k
1) square both sides to get u^2=1+x 2) then bring over the 1: you'd get u^2-1=x 3) differentiate both sides: (2u)du=dx 4) sub back into main equation:
Integral x*sqrt(x+1)dx =Integral[ (u^2-1)(u)(2u)du] = Integral [(u^2-1)(2u^2)du]= intergral [2u^4 - 2u^2]du and then you can intergrate simply and substitute u=sqrt(1+x) back into the equation to obtain the